2009
DOI: 10.1016/j.antiviral.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Wanted, dead or alive: New viral vaccines

Abstract: Vaccination is one of the most effective methods used for protecting the public against infectious disease. Vaccines can be segregated into two general categories; replicating vaccines (i.e., live, attenuated vaccines) and non-replicating vaccines (e.g., inactivated or subunit vaccines). It has been assumed that live attenuated vaccines are superior to non-replicating vaccines in terms of the quality of the antiviral immune response, the level of protective immunity, and the duration of protective immunity. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 106 publications
(121 reference statements)
0
36
0
1
Order By: Relevance
“…The control of latent viral infections [including cytomegalovirus (CMV), varicella zoster virus (VZV), Epstein-Barr virus (EBV), and Herpes Simplex virus (HSV)] is associated with cell-mediated immune responses, indicating that measures of cellular immunity should make ideal correlates of protection for these diseases. Advances in critical elements of vaccinomics (pathogen biology, epitope identification, and host response) have furthered our understanding of key targets of protective immunity, critical gene and pathways activated during immune responses, and appropriate endpoints and measures of clinical efficacy, thereby opening the door to improving current vaccines and creating next-generation vaccines against difficult pathogens such as tuberculosis, francisella, plague, malaria, subunit-based vaccines and, just as importantly, improved measures of protection and vaccine efficacy (Amanna and Slifka, 2009;de Boer et al, 2010;Vaine et al, 2010).…”
Section: The Case Of Vaccine Clinical Testing Biomarkersmentioning
confidence: 99%
“…The control of latent viral infections [including cytomegalovirus (CMV), varicella zoster virus (VZV), Epstein-Barr virus (EBV), and Herpes Simplex virus (HSV)] is associated with cell-mediated immune responses, indicating that measures of cellular immunity should make ideal correlates of protection for these diseases. Advances in critical elements of vaccinomics (pathogen biology, epitope identification, and host response) have furthered our understanding of key targets of protective immunity, critical gene and pathways activated during immune responses, and appropriate endpoints and measures of clinical efficacy, thereby opening the door to improving current vaccines and creating next-generation vaccines against difficult pathogens such as tuberculosis, francisella, plague, malaria, subunit-based vaccines and, just as importantly, improved measures of protection and vaccine efficacy (Amanna and Slifka, 2009;de Boer et al, 2010;Vaine et al, 2010).…”
Section: The Case Of Vaccine Clinical Testing Biomarkersmentioning
confidence: 99%
“…The majority of current vaccines consists of live, attenuated, or inactivated pathogens that were developed in the past by empirical approaches (1). Understanding vaccine-mediated correlates of immunity is critical for the rational design of novel pathogen-free vaccines against diseases caused by complex pathogens -such as malaria, tuberculosis, or HIV/AIDS, for which no effective vaccine currently exists -or to improve the safety and/or efficacy of existing vaccines (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Licensed human vaccines for flaviviruses include formaldehyde-inactivated vaccines against TBEV and JEV as well as a live, attenuated vaccine against YFV. Although cellular immunity plays an important role in clearing primary WNV infection [5-9], memory CD8 + T cells are dispensable if high levels of antiviral antibody are present [7] and vaccine-induced memory T cells may not play a substantial role in controlling flavivirus infection in humans [10]. Moreover, a number of studies using passive immunization have shown that transfer of neutralizing antibodies to naïve animals is sufficient for protection against lethal WNV infection [11-15].…”
Section: Introductionmentioning
confidence: 99%